Sheep dung input enhances arthropod biomass and a threatened insectivorous bird: Experimental management for conservation - Margarita Reverter; Juan Traba; Adrián Barrero; Daniel Bustillo‐de la Rosa; Julia Gómez‐Catasús; Julia Zurdo; Cristian Pérez‐Granados (Ecological Solutions and Evidence)
Abstract In recent decades, Europe has seen a notable decrease in extensive grazing by domestic livestock; endangering semi‐natural open habitats; and impacting soil, vegetation, arthropods and insectivores. Despite the known ecological consequences of grazing decline, little research has explored the role of sheep dung in influencing plant cover, arthropod biomass and higher trophic levels, such as insectivorous birds. To address this gap, a 3‐year study (2017–2019) was conducted in a Mediterranean shrub‐steppe in central Spain. Two 10‐hectare non‐grazed experimental plots received different doses of sheep dung, while a grazed area served as a reference. Vegetation structure was assessed annually, arthropods were sampled six times per year and the breeding space use of a threatened insectivorous bird was estimated annually. While dung input did not affect vegetation structure, it had short‐term positive effects on some arthropods, particularly epigeous and coprophagous species. Additionally, the insectivorous bird increased its use of space in response to dung application, likely due to the rise in arthropod biomass, a critical food resource. In areas where sheep grazing is declining, sheep dung inputs may serve as an effective short‐term strategy to increase the biomass of specific arthropod groups, indirectly benefiting their predators. Further research is needed to assess long‐term effects on arthropod communities and a wider range of insectivorous species, aiding conservation efforts in areas facing low grazing pressures.